Pendampingan ibu - ibu PKK tentang Deteksi Kanker Serviks Melalui Software Aplikasi - Hidayat, Erwin Yudi; Astuti, Yani Parti; Salam, Abu; Nugraha, Adhitya; Paramita, Cinantya; Octaviani, Dhita Aulia (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
One feared cancer among mothers is cervical cancer. Cervical cancer is a type of cancer that occurs in the cervix of women. Due to its hidden location, women may not be able to detect early on whether they have cervical cancer or not. Meanwhile, this disease ranks among the top three causes of death in Indonesia. To determine early on whether a woman is affected by cervical cancer, various methods are employed. Some search for symptoms on social media, some take preventive measures with various herbal remedies to avoid cervical cancer, and many other actions are taken by women. With the touch of artificial intelligence technology, these issues can be addressed. Therefore, the dedicated team is trying to create an application that can detect cervical cancer. With this application, women can find out early on whether they have or are approaching cervical cancer. Although the accuracy of this application is not 100%, at least women can be aware of the detection of this disease and can promptly seek treatment or prevention. With the existence of this application, it is hoped that it can be beneficial for the mothers of PKK Perum Kandri Persona Asri RT 04 RW 04, who are the subjects of this dedication.